Peran Bank Garansi dalam Mengurangi Risiko Bisnis pada Proyek Konstruksi di Indonesia - Rosiga, Fonnyta Laurenzia (Journal of Economic and Business Law Review, 2024)
The banking and construction industry has a strategic role in supporting economic stability and growth in Indonesia. Bank guarantee as one of the important instruments in the banking sector, provides guarantees to the recipient of customer obligations. In the construction industry, bank guarantees are used to mitigate risks in infrastructure development projects. However, the regulations governing the bank guarantee mechanism are still general and not detailed, giving rise to many interpretations and deviations. This affects dispute resolution, project implementation, and trust between the parties involved. On the other hand, challenges in the construction industry, such as project delays, contract disputes, and regulatory complexity, are also obstacles in supporting national development. Therefore, it is necessary to prepare more detailed regulations and standardize operational procedures related to bank guarantees, as well as strengthen supervision and professionalism in the construction industry, to create legal certainty, efficiency, and sustainability of national infrastructure development. The method used in this study is normative. Relevant legislative and conceptual approaches.